2008
DOI: 10.1210/en.2008-0404
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide and Respiratory Coupling in Mitochondria of Insulin-Deficient Diabetic Rats

Abstract: Mitochondrial reactive oxygen species have been implicated in both diabetic complications and the progression of the underlying diabetic state. However, it is not clear whether mitochondria of diabetic origin are intrinsically altered to generate excess reactive oxygen species independent of the surrounding diabetic milieu. Mitochondria were isolated from gastrocnemius, heart, and liver of 2-wk and 2-month streptozotocin diabetic rats and controls. We rigidly quantified mitochondrial superoxide, respiration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 59 publications
6
62
2
2
Order By: Relevance
“…Data for ROS production, proton conductance, and oxygen consumption from 34 rats (17 control and 17 STZ-diabetic), comprising groups II and III of a previous publication (15), has previously been reported in that manuscript. Here, we combine these results with 57 newly studied animals (26 control and 31 STZ-diabetic), increasing the numbers for data comparison and enabling adequate numbers to assess ROS in relation to multiple mitochondrial functional parameters assessed under different substrate and inhibitor conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data for ROS production, proton conductance, and oxygen consumption from 34 rats (17 control and 17 STZ-diabetic), comprising groups II and III of a previous publication (15), has previously been reported in that manuscript. Here, we combine these results with 57 newly studied animals (26 control and 31 STZ-diabetic), increasing the numbers for data comparison and enabling adequate numbers to assess ROS in relation to multiple mitochondrial functional parameters assessed under different substrate and inhibitor conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle and heart tissues were minced for 1 min prior to homogenization. Mitochondria were then isolated and washed three times, as previously described (11,15,17). Mitochondria prepared in this fashion were highly pure, as indicated by the distribution of glyceraldehyde-3-phosphate dehydrogenase and porin in whole tissue and mitochondrial extracts (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have revealed important differences between models of type 1 and type 2 diabetes. Mitochondrial reactive oxygen species (ROS) production is increased in the hearts of type 2 diabetic models, whereas type 1 diabetic models show no increase or even reduced production of ROS that originate from mitochondria Herlein et al, 2009). Fatty acid-induced mitochondrial uncoupling is another trait of type 2 diabetic hearts that does not seem to be present in type 1 diabetic models .…”
Section: Rodent Models Of Diabetic Cardiomyopathymentioning
confidence: 99%
“…Studies investigating oxidative stress in STZ-diabetic hearts revealed increased cellular ROS levels, enhanced superoxide production, increased NADPH oxidase expression (subunit p47) and decreased GSSG/GSH ratios (ratio of oxidized to reduced glutathione) (Ghosh et al, 2004;Ghosh et al, 2005;Ceylan-Isik et al, 2006;Lashin et al, 2006;Wold et al, 2006;Singh et al, 2008). The mitochondrial origin of increased superoxide remains controversial because direct measurements of mitochondrial superoxide production showed no increase in STZ hearts (Herlein et al, 2009 (Lopaschuk et al, 1983;Flarsheim et al, 1996;Hattori et al, 2000;Choi et al, 2002;Zhao et al, 2006;Suarez et al, 2008). Furthermore, several studies have demonstrated increased connective tissue content in STZ-diabetic hearts, which can be attenuated by treatment of mice with the aldosterone antagonist spironolactone, suggesting that increased aldosterone action may contribute to cardiac fibrosis (Miric et al, 2001;Westermann et al, 2007;Singh et al, 2008;Ueno et al, 2008;Van Linthout et al, 2008).…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%